Heart failure - James A. Ker (South African Family Practice)
Heart failure is a clinical syndrome that can result from any structural or functional cardiac disorder that impairs the performance of the ventricle: either to eject blood (systolic dysfunction) [or reduced ejection function] or to fill with blood (preserved ejection fraction or diastolic heart failure).